Association between perinatal anemia and postpartum depression: A prospective cohort study of Japanese women. Issue 1 (9th October 2019) - Maeda, Yuto; Ogawa, Kohei; Morisaki, Naho; Tachibana, Yoshiyuki; Horikawa, Reiko; Sago, Haruhiko
Abstract: Objective: To clarify the association between postpartum depression (PPD) and anemia in each stage of pregnancy as well as in the postpartum period. Methods: A prospective cohort study was conducted between May 2010 and November 2013 at a tertiary hospital in Japan. In total, 1128 women were assessed using the Edinburgh Postpartum Depression Scale (EPDS) at postpartum week 4 and a blood test was performed in the second trimester (24–28 weeks of gestation), third trimester (35–36 weeks of gestation), and postpartum week 1. The primary outcome was PPD, defined as an EPDS score of 9 or higher. Multivariate logistic regression analysis was used to elucidate the association between anemia and PPD for each period. Additionally, trend analysis was conducted to determine if there was a linear association between maternal hemoglobin concentration and PPD. Results: Postpartum anemia was significantly associated with increased PPD risk (adjusted odds ratio 1.63, 95% confidence interval 1.17–2.26) whereas anemia in the second and third trimesters was not. Similarly, a significant inverse association was observed between the quintiles of maternal hemoglobin levels in the puerperium and the PPD risk ( P value for trend 0.004). Conclusion: Postpartum anemia was associated with an increased risk of PPD. Abstract : Postpartum depression was associated with anemia in the postpartum period but not in the second or third trimester.